Which Tools Can Aid the Management of Intangible Cultural Heritage in Community Based Heritage Organizations in Cairo? A Case Study of Shubra’s Archive - Zwemstra, Mienke (AUC Knowledge Fountain, 2024)
This thesis provides a comprehensive overview of cultural heritage management in Cairo, focusing particularly on intangible heritage and the potential benefits of digital tools in this field. It highlights the marginalization of community-based organizations in the broader narrative of heritage management in Cairo, along with the limited alignment and collaboration between local, national and international heritage institutions. Drawing from ethnographic research conducted at the Shubra’s Archive (SARD), this study identifies the challenges faced by such organizations, including the reliance on volunteers and international funding for mission implementation. It emphasizes the importance of strategic planning and collaboration with municipal and national entities to further the goals of community-based heritage management initiatives. The study also delves into the potential of digital tools in heritage management, highlighting their positive impact when implemented at the grassroots level. Based on empirical insights and conversations with SARD's founder and volunteers, strategic recommendations are offered to enhance the organization's effectiveness and sustainability. These recommendations include continued digitization efforts, community engagement, and collaboration with governmental bodies and other stakeholders. Looking ahead, the study advocates for ongoing research and innovation in heritage management. It emphasizes the importance of continual collaboration and adaptation to evolving contexts, both locally and globally, to ensure the preservation and promotion of intangible heritage in Cairo.